Serum Asymmetric Dimethylarginine Levels in Patients with Acute Rheumatic Fever - Sert, Ahmet; Cimen, Derya; Arslan, Derya; Aypar, Ebru; Vatansev, Husamettin; Kaya, Fatma; Kilicaslan, Cengizhan; Aslan, Eyup; Guvenc, Osman; Gun, Fatmagul; Oran, Bulent; Odabas, Dursun (Journal of Pediatric Biochemistry, 2015)
Asymmetric dimethylarginine (ADMA) is an analogue of l-arginine, a naturally occurring product of metabolism found in human circulation. It is an endogenous inhibitor of nitric oxide production. Acute rheumatic fever (ARF) is a delayed immunologically mediated autoimmune sequel of throat infection by group A β-hemolytic streptococci. As serum ADMA levels have not previously been assessed in patients with ARF, we aimed to investigate ADMA levels in patients with ARF during the acute stage and after anti-inflammatory treatment and compared results with healthy control subjects. The study population consisted of 34 children with ARF (30 patients with carditis and 4 patients without carditis) and 31 healthy control subjects. Erythrocyte sedimentation rate and C-reactive protein values were significantly higher and serum ADMA values were lower, but not statistically significant in patients with ARF during the acute stage when compared with controls. Serum C-reactive protein and erythrocyte sedimentation rate values were significantly decreased in patients with ARF after the treatment when compared with baseline and ADMA levels were increased after the treatment compared with baseline, but this change was not statistically significant. Our study has demonstrated that resolution of acute inflammation in patients with ARF may lead to a mild increase in serum concentration of ADMA. Comprehensive prospective and observational studies are required to confirm our findings and to assess potential interactions between ARF and ADMA levels.
Keywords: acute rheumatic fever; asymmetric dimethylarginine; carditis